Performance evaluation of expenditure in primary care: the case of Brazil’s southeastern cities - Santos, Lucas Maia dos; Gonçalves, Márcio Augusto; Ferreira, Marco Aurélio Marques (Organizações & Sociedade, 2014)
This study aimed to analyze the performance of cities of Brazil’s southeastern region on primary care expenditure, from 2007 to 2010. In order to do the performance analysis we used the technical efficiency scores produced by the Data Envelopment Analysis (DEA) methodology and the Ray and Desli Malmquist Index as the quantitative metrics. Before starting the cities’ efficiency analysis, the cluster analysis was applied to group similar cities. This study proposes an analytical model of the comparative performance of 1097 cities, based on the National Primary Care Policy. The efficiency scores obtained highlights the disparities in the allocation of resources and lost in productivity through the years analyzed. This fact could be justified due the absence of procedures of relative comparison between cities and the decentralization of public expenses in public healthcare. The results shed light on the possibility to improve the quantity of primary care services, given the current level of expenditure.